2023
DOI: 10.1002/cbdv.202200890
|View full text |Cite
|
Sign up to set email alerts
|

Inula viscosa (L.) Aiton Ethanolic Extract Inhibits the Growth of Human AGS and A549 Cancer Cell Lines

Abstract: The present study shows the chemical profile and cytotoxic properties of the ethanolic extracts of Inula viscosa from Northeast Algeria. The extract was obtained by maceration using ethanol. Its phenolic profile was determined using ultra-high-performance liquid chromatography coupled with a diode array detector and an electrospray mass spectrometer (UHPLC-DAD-ESI/MS), which allowed the identification and quantification of 17 compounds, 1,5-O-caffeoylquinic acid being the most abundant. The cytotoxic activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 82 publications
(160 reference statements)
1
8
0
Order By: Relevance
“…These findings obtained in this study correlate with in vitro cytotoxicity results of Anula viscosa extract, a plant species belonging to the same genus as S. viscosa , the ethanolic extract of Anula viscosa was reported to have antiproliferative activity by inhibiting the proliferation of human gastric cancer cells (AGS) by 60 % and human lung cancer (A549) cells by 40 % [60] . The antiproliferative activity of S. viscosa observed in this study can be attributed to the identified compounds such as Phytol ( 7 ) with the GC/MS technique.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…These findings obtained in this study correlate with in vitro cytotoxicity results of Anula viscosa extract, a plant species belonging to the same genus as S. viscosa , the ethanolic extract of Anula viscosa was reported to have antiproliferative activity by inhibiting the proliferation of human gastric cancer cells (AGS) by 60 % and human lung cancer (A549) cells by 40 % [60] . The antiproliferative activity of S. viscosa observed in this study can be attributed to the identified compounds such as Phytol ( 7 ) with the GC/MS technique.…”
Section: Resultssupporting
confidence: 84%
“…[76] B16F10 skin and COLO205 colon cancer cells were incubated at a concentration of 1x10 4 cells/mL in a culture medium at 37 °C with 5 % CO 2 for 24 h. The cells were seeded at a density of 104 cells/well in 100 μL of culture medium in microplates. Subsequently, the cells were exposed to various concentrations (20,40,60,80, and 100 μg/mL) of the 80 % ethanolic extract solution. Wells with DMSO (0.2 % in PBS) were used as controls, and the samples were incubated in triplicate.…”
Section: In Vitro Anti-inflammatory Activitymentioning
confidence: 99%
“…[67] Caffeic acid is known to arrest cell cycle in a dose-and time-dependent manner and activate apoptosis, [68][69][70] while quercetin, a flavonoid present in propolis, inhibits the growth of human lung adenocarcinoma cell lines (A549 and HCC-44) [71] and JB6 P + cells [72] by inducing caspase-3-dependent apoptosis. [73][74][75] Ferulic acid was shown to modulate several molecular pathways involved in a multitude of biological functions. Accordingly, ferulic acid was shown to reverse multiple drug resistance against paclitaxel, [76] and regulated epithelial-to-mesenchymal transitions resulting in the inhibition of metastasis in MDA-MB-231 breast carcinoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…QN is the main active ingredient in drugs used to treat malaria, and it also has analgesic, antipyretic, and antiinflammatory properties. , In addition, QN is utilized as a flavoring agent and provides bitterness in soft drinks. , QD is the enantiomer of QN, which can also be employed in the treatment of malaria and arrhythmias in clinical applications. Excessive use of QN and QD can cause many side effects, such as nausea, headache, asthma, kidney failure, and nerve and cardiovascular damage. Up to now, some methods for determining QN and QD are high-performance liquid chromatography, , chemiluminescence, , atomic absorption spectrometry, , and electrochemical analysis. , Nevertheless, these analytical methods are not very effective in distinguishing two enantiomers and have the disadvantages of high cost, complex preconditioning, and time consumption. Therefore, a quick, convenient, and economical detection method is necessary but challenging in the field of monitoring QN and QD.…”
mentioning
confidence: 99%
“…Excessive use of QN and QD can cause many side effects, such as nausea, headache, asthma, kidney failure, and nerve and cardiovascular damage. 5−7 Up to now, some methods for determining QN and QD are highperformance liquid chromatography, 8,9 chemiluminescence, 10,11 atomic absorption spectrometry, 12,13 and electrochemical analysis. 14,15 Nevertheless, these analytical methods are not very effective in distinguishing two enantiomers and have the disadvantages of high cost, complex preconditioning, and time consumption.…”
mentioning
confidence: 99%